Surat Al-Fātiḥah: Etika dalam Estetika Membaca Ummul Kitab dengan Pendekatan Retorika dan Stilistika - Busthami Ibrohim; Rizzaldy Satria Wiwaha; Lalu Turjiman Ahmad (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2021)
This article studies Al-Fātiḥah, the first Surah of the Alquran. As the opening of the Alquran, by which the name indicates, Al-Fātiḥah represents the whole contents of the Holy Book, thus, it is also named as Ummu l-Kitāb. In addition to Prophetic traditions informing the fuction of the Surah as invocation, these facts can explain the reason why it is very close to Muslims’ life, and has deserved interpraters’ attention. Nevertheless, apart from this familiarity, the main problem to question in this small research is concerning the use of praise (to God) preceeding every invocation, as this Surat shows. By employing Rhetoric and Stylistic approaches, this study focuses on Surah al-Fātiḥah in regards with its aspects of phonetic, word forms, wordings, and word positioning in the structure of every single sentence, to be able to grasp the aesthetics of the Sūrah as well as the doctrines contained therein as ethical values. The results of the study show that Sūrah al-Fātiḥah poses high level of aesthetics, by employing various language styles such as, to mention some, anastrophe (taqdīm wa ta’khīr) and “enallage” (iltifāt). This Surah also contains lots of essence, and one of the most important in this regard is to be respectful during communication with the other.